Some notes on the fundamental legal concepts in the work of Wesley Hohfeld and Carlos Cossio. A dialogue with María Beatriz Arriagada Cáceres - Luna, Diego (2023)
In this article I explore the possibilities of a dialogue as a methodology and offer, as a contribution, an attempt to reconcile apparently dissimilar conceptual schemes around the same theoretical problem, namely, that of the so-called fundamental legal concepts and their usefulness at the level of legal logic based on the conceptual categories developed by Wesley Hohfeld (1879-1918) and Carlos Cossio (1903-1987).